A Decision Model of Therapy for Potentially Resectable Pancreatic Cancer - VanHouten, Jacob P.; White, Rebekah R.; Jackson, Gretchen Purcell (The Journal of surgical research, 2012)
Optimal treatment for potentially resectable pancreatic cancer is controversial. Resection is considered the only curative treatment, but neoadjuvant chemoradiotherapy may offer significant advantages. We developed a decision model for potentially resectable pancreatic cancer. Initial therapeutic choices were surgery, neoadjuvant chemoradiotherapy, or no treatment; subsequent decisions offered a second intervention if not prohibited by complications or death. Payoffs were calculated as the median expected survival. We gathered evidence for this model through a comprehensive MEDLINE search. One-way sensitivity analyses were performed. Neoadjuvant chemoradiation is favored over initial surgery, with expected values of 18.6 and 17.7 mo, respectively. The decision is sensitive to the probabilities of treatment mortality and tumor resectability. Threshold probabilities are 7.0% mortality of neoadjuvant chemoradiotherapy, 69.2% resectability on imaging after neoadjuvant therapy, and 73.7% resectability at exploration after neoadjuvant therapy, 92.2% resectability at initial resection, and 9.9% surgical mortality following chemoradiotherapy. The decision is sensitive to the utility of time spent in chemoradiotherapy, with surgery favored for utilities less than 0.3 and −0.8, for uncomplicated and complicated chemoradiotherapy, respectively. The ideal treatment for potentially resectable pancreatic cancer remains controversial, but recent evidence supports a slight benefit for neoadjuvant therapy. Our model shows that the decision is sensitive to the probability of tumor resectability and chemoradiation mortality, but not to rates of other treatment complications. With minimal benefit of one treatment over another based on survival alone, patient preferences will likely play an important role in determining best treatment.